STPA analysis for safe operation of maritime autonomous surface ship under degradation state - Park, Hyeri; Kim, Jeongmin (Frontiers in Marine Science, 2025)
As Maritime Autonomous Surface Ships (MASS) move toward commercialization, ensuring operational safety under degraded states has emerged as a critical challenge. This study conducts a risk analysis to identify hidden hazards that may occur when MASS operate in degraded states—conditions where the ship stays within the operational environment (OE) but outside its operational design domain (ODD). The analysis applies the System-Theoretic Process Analysis (STPA) methodology, focusing on the interactions among MASS, Remote Operations Centers (ROC), and Remote Operators (ROs) as defined in the MASS code being enacted by the International Maritime Organization (IMO). STPA modeling reveals that loss of situational awareness, information asymmetry, delayed commands, and failures in inter-system coordination are primary risk factors during degraded conditions. Based on the analysis, the study identifies control actions and safety constraints to address these hazards and proposes practical safety guidelines. These findings contribute to the development of risk-based operational modes and standards to support the safe navigation of MASS, even in degraded states.